Subcutaneous mepolizumab in children aged 6 to 11 years with severe eosinophilic asthma. Issue 12 (9th September 2019) - Gupta, Atul; Pouliquen, Isabelle; Austin, Daren; Price, Robert G.; Kempsford, Rodger; Steinfeld, Jonathan; Bradford, Eric S.; Yancey, Steven W.
Abstract: Objectives: There are no published reports for anti‐interleukin‐5 therapy in children <12 years with asthma. The primary objective of this study was to characterize the pharmacokinetics and pharmacodynamics of mepolizumab following subcutaneous (SC) administration in children 6 to 11 years‐of‐age with severe eosinophilic asthma. Hypothesis: Mepolizumab SC pharmacokinetics and pharmacodynamics in children with severe eosinophilic asthma are comparable with adults. Study Design: Multinational, nonrandomised, open‐label (NCT02377427). Patient Selection: Children 6 to 11 years‐of‐age with severe eosinophilic asthma (blood eosinophil count ≥150 cells/µL at screening or ≥300 cells/µL <12 months of screening) and ≥2 exacerbations in the prior year. Methodology: Children received mepolizumab SC 40 mg (bodyweight <40 kg) or 100 mg (≥40 kg) every 4 weeks for 12 weeks. Results: Thirty‐six children received mepolizumab (40 mg, n = 26; 100 mg, n = 10). Mepolizumab exposures were higher and apparent clearance lower than predicted based on prior existing data. Derived mepolizumab exposures normalized to mean bodyweight for the 40 mg and 100 mg dose groups were 454 μg * day/mL and 675 μg * day/mL, respectively. At week 12, blood eosinophils were reduced by 89% and 83% from baseline to 42 and 55 cells/µL, respectively. Mepolizumab was well tolerated; no new safety signals were observed compared with previous adult/adolescent studies. Conclusion: In children 6 to 11 years‐of‐age with severe eosinophilic asthma, mepolizumab SC 40 or 100 mg provided bodyweight‐adjusted drug exposure within twofold of target adult exposure as well as marked reductions to blood eosinophil counts similar to adults, and although not designed to evaluate efficacy outcomes, demonstrated a positive clinical profile.